Robot in the loop indoor tug-of-war : mechanical interface - Gonia, Stefan (2017)
This report describes the in-depth study, research, construction of hardware, development of software and testing done during the whole 2 Semester period of the Final Year Project (FYP) Programme. In fulfilment of the project, student is expected to work with fellow NTU Final Year students as a team in building a Tug of War machine robot. Tug-of-war is one of the most ancient/traditional test of strength game that involves two opposing parties pulling at opposite ends of a rope. The inspiration of this project is to build a new creative tug of war game which is suitable to be played either indoor and/or outdoor. Students are given full freedom to explore on how to approach and build the system design. Based on the project direction, a development task is being assigned to explore on the mechanical interface of the system design. After various brainstorming sessions, from the various ideas generated, a 3-way tug of war game system was chosen as one of the design concept to be explored further and developed. Various design prototypes were constructed, developed and tested by hand. The design prototype was built mainly using wood materials. To enhanced the user experience in playing the game, an embedded system integrated with various sensors was developed and tested in the process. Testing of these design prototypes was done by simulating various possible scenarios of a game play. The recorded results were then observed. From this test, it was found that the design concept is behaving in a similar manner as what it is in theory. Thus, it was concluded that this particular design concept is potentially one of the creative ways in playing a tug of war game.